2022
DOI: 10.1128/jvi.00455-22
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Characterization of SARS-CoV-2 Spike Protein in Virus-Infected Cells Using the Receptor Binding Domain Binding Specific Human Monoclonal Antibodies

Abstract: The SARS-CoV-2 spike (S) protein receptor binding domain (RBD) mediates the attachment of SARS-CoV-2 to the host cell. This interaction plays an essential role in initiating virus infection, and the S protein RBD is therefore a focus of therapeutic and vaccine interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 59 publications
(74 reference statements)
5
11
1
Order By: Relevance
“…On this basis and by default, we therefore concluded that the PD4 and sc29 antibodies bind to the S protein at sites located within the S2 domain rather than the S1 domain. This is consistent with our previous study that demonstrated high binding affinity of the PD4 and sc29 antibodies to the S protein, but that they did not bind to the purified RBD and nor did they exhibit virus neutralising activity [17].…”
Section: Determining the S Protein Subunit Binding Specificity Of The...supporting
confidence: 93%
See 4 more Smart Citations
“…On this basis and by default, we therefore concluded that the PD4 and sc29 antibodies bind to the S protein at sites located within the S2 domain rather than the S1 domain. This is consistent with our previous study that demonstrated high binding affinity of the PD4 and sc29 antibodies to the S protein, but that they did not bind to the purified RBD and nor did they exhibit virus neutralising activity [17].…”
Section: Determining the S Protein Subunit Binding Specificity Of The...supporting
confidence: 93%
“…2D). Based on the staining intensity exhibited by the transfected cells we concluded that both sc23 and PD5 exhibited similar binding properties to the S1 domain, which is consistent with sc23 and PD5 exhibiting similar binding affinities for the S protein in our previous study [17]. However, in this current study we failed to detect sc23-staining in the RBD-expressing cells, suggesting that sc23 binds to other regions of the S1 protein subunit that are distinct from the RBD.…”
Section: Determining the S Protein Subunit Binding Specificity Of The...supporting
confidence: 90%
See 3 more Smart Citations